SALES LAW BEYOND SALES CONTRACTS: APPLICABILITY AND APPLICATIONS OF THE CISG TO NON-SALES TRANSACTIONS (THE CASE OF COUNTERTRADE AND BARTER TRANSACTIONS) - Torsello, Marco (Journal of Law and Commerce, 2020)
n/a